The Relationship Of Incident Insomnia With The Level Of Depression In The Elderly At Panti Sosial Tresna Wredha (PSTW) Jember - Habiburrahman, Dwi; Sofia Rhosma; Wahyudi Widada (Indonesian Journal Publisher, 2025)
Insomnia is a sleep disorder in the elderly that can cause depression. The prevalence of insomnia in the elderly is quite large, with 50% of the total elderly population experiencing insomnia. The aim of this study was to determine the relationship between the incidence of insomnia and the level of depression in the elderly at the Tresna Werdha Social Services UPT (PSTW) Jember. Correlational research design with a cross sectional approach. The population in this study were 62 elderly people at UPT PSTW Jember with independent daily activities. The sampling technique in research uses cluster sampling. The number of samples based on the results of the fraction per cluster formula calculation was 54 people. This research was conducted in October-November 2023. The data collection technique used a questionnaire. The relationship between the incidence of insomnia and the level of depression in the elderly at UPT PSTW Jember using Spearmen Rho statistical analysis. The research results showed that 43 elderly were women, 50 elderly aged 70-80 years, 51 elderly whose marital status was divorced and discontinued and 45 elderly did not go to school. The statistical test results show that ρ value = 0.000 with α = 0.05. This explains that there is a relationship between the incidence of insomnia and the level of depression in the elderly at UPT Social Services Tresna Werdha (PSTW) Jember.